The Effectiveness of Scratch Learning Media Using the PMRI Approach to Improving Students’ Learning Outcomes - Fransiska Januarti Gusman; Ikrar Pramudya; Riyadi (Universitas Pendidikan Ganesha, 2023)
In the process of learning mathematics, the teacher always strives for the material presented to be well understood by students, with the intention that the objectives of learning can be achieved properly. This study aimed to analyze the effectiveness of scratch learning media with the PMRI approach in improving student learning outcomes. The type of research used was research and development referring to the ADDIE model. The development stage consists of 3 stages: preliminary stage, development stage, and testing stage. The data collection instrument used expert validation sheets, student and teacher response questionnaires, and test questions. The process of effectiveness through validation on scratch learning media with the PMRI approach and also measuring the practicality of scratch media with the PMRI approach through student and teacher response questionnaires, while the effectiveness of scratch learning media with the PMRI approach through the test given questions. The results obtained showed that the scratch learning media with the PMRI approach is declared valid with an average score of 70.28% in the valid category. Scratch learning media with the PMRI approach was said to be practical with an average score of 82.61% in the very practical category. Scratch learning media with effective criteria from learning test results with a score of 2.1286 > 2.0057 which meant learning outcomes using scratch learning media with the PMRI approach were better than learning outcomes without using scratch learning media with the PMRI approach, so that scratch learning media with the PMRI approach was effective in improving learning outcomes.